Knowledge, Attitudes, and Practices on Antibiotic Use: Inputs to the Development of Educational Materials on Antibiotics - Jane M. Tagum-Briones; Cyril B. Romero; Luzviminda V. De Villa; Urfa K. Hisan (The Indonesian Institute of Science and Technology Research, 2023)
This research study was designed to determine the knowledge, attitudes, and practices on antibiotic use among patients of Rural Health Units in the 5th Congressional District of Camarines Sur, Philippines. Specifically, it aimed to determine the relationship between the demographic profile of the patients and the knowledge, attitudes, and practices on antibiotic use. We also analyze the relationship between the factors that influence antibiotic use and the knowledge, attitudes, and practices and develop educational materials for awareness campaign and counseling. This study uses the descriptive-survey method, of which the questionnaire as the primary data gathering tool supplemented by guided interviews. We used the quota sampling method to determine the 350 respondents in the study. We selected 50 patients from each municipality using the convenience method. Most of the patient’s antibiotics use were highly influenced by the financial problem or personal factors, environmental factors, lack of knowledge and information on antibiotics, and socio-economic factors. The personal, environmental, and socio-economic factors that influence antibiotic use are significantly related to the patients' knowledge, attitudes, and antibiotic use practices. The educational materials developed in the study may enhance the level of awareness upon its utilization during educational campaign and patients counseling.